Examining cellular responses to reconstituted antibody protein liquids - M. Tyler Nelson (Nature Portfolio, 2021)
Abstract Protein ionic liquids (PIL) are a new class of biologic stabilizers designed to protect the functionality and extend the shelf-life of biotechnological and therapeutic agents making them more readily available, and resistant to austere environments. Protein biorecognition elements such as monoclonal antibodies are commonly utilized therapeutics that require the robust stabilization offered by PILs, but biocompatibility remains an important issue. This study has focused on characterizing the biocompatibility of an antibody based PIL by exposing multiple cells types to a cationized immunoglobulin suspended in an anionic liquid (IgG-IL). The IgG-IL caused no significant alterations in cellular health for all three cell types with treatments < 12.5 µg/mL. Concentrations ≥ 12.5 µg/mL resulted in significant necrotic cell death in A549 and HaCaT cells, and caspase associated cell death in HepG2 cells. In addition, all cells displayed evidence of oxidative stress and IL-8 induction in response to IgG-IL exposures. Therapeutic Ig can be utilized with a wide dose range that extends into concentrations we have found to exhibit cytotoxicity raising a toxicity concern and a need for more extensive understanding of the biocompatibility of IgG-ILs.